TINJAUAN HUKUM INTERNASIONAL MENGENAI EKSISTENSI KONSUL KEHORMATAN (HONORARY CONSUL) DALAM HUBUNGAN KONSULER (STUDI KASUS: KONSUL KEHORMATAN JERMAN DI MEDAN) - Kania Syafiza; Arif Arif; Jelly Leviza (Journal of USU International Law, 2014)
Abstract Regarding of the implementation of peaceful relations between countries, which generally marked by the opening of diplomatic relations  and in addition followed by the opening of consular relations. Diplomatic relations are political while consular relations is non-political and tends to take care of administrative and commercial issues. To carry out consular functions in a foreign country who establishes consular relations with it, a country appointed  the consular officer.  Vienna Convention 1963 classifies consular officials into namely Career Consular Officers and Honorary Consular Officers. Indonesia and Germany have officially established diplomatic relations since 1952 and at present Germany representatives in Indonesia consists of an embassy and three Honorary Consuls, one of which located in Medan. The scope of consular relations by  Germany Honorary Consul in Medan consists of honorary consulate opening, the appointment of honorary consuls and operational matters of consular relations  by the honorary consul. Tasks and functions of the of Germany Honorary Consul in the field are based on the provisions contained in Konsulargesetz which is an affirmation of the Vienna Convention 1963. While the immunity and privileges acquired  by Germany Honorary Consul in Medan in carrying out its tasks and functions are very limited. It is recommended for reasons of economy and efficiency, the appointment of honorary consuls may be the right choice for countries that want to open a consular representative at the present time. In carrying out its tasks and functions, Germany Honorary Consul in Medan can enhance its role as a liaison of the business activities between Germany and Indonesia. Therefore, in terms of granting immunities and privileges of the Honorary Consul, Indonesia and Germany should make a special agreement on the matter in order to ensure a honorary consul can carry out his functions without a hitch Keyword: diplomatic, consular, relation